RELATIONSHIP OF KNOWLEDGE OPERATIONS CONCEPT OF ROUND NUMBERS TO MATHEMATICAL ACHIEVEMENT OF HIGH CLASS STUDENTS IN SD INPRES LELUMPANG - Mufidah Mufidah (Jurnal Dikdas, 2019)
The The purpose of this study wasto determine relationship between knowledge of concept of round number operation on students’ learning achievement of mathematics in high class. This research method uses descriptive quantitative type with the subject of research is all students of class IV in SD Inpres Lelumpang, which amounted to 15 people, consisting of 10 men and 5 women.Data collection is done by angket,tests,interviews, and documentation. The results showed that of 15 students, there are 2 students or 13,33% who had knowledge of the concept of rounded operation is very good , there are 15 students there are 4 students or 26,67% who stated the knowledge of concept of round number operation good.and of 15 students there are 9 students or 60% who stated the knowledge of concept of round number operation enough.While student achievement of 15 students there are 1 students or 6,6 % learning achievement is very good and of 15 students, there are 4 students or 26,67 % percentage of good learningand of 15 students, there are 10 students or 66,67 % percentage of enough learning.Based on the data found in this study, that correlational analysis consulted at a significant level of a=95% obtained r arithmetic > r table or 0,5602> 0,514. It means Ha (alternative hypothesis) is rejected. So it can be concluded that there is a positive and significant Relationship Between Knowledge of Concept of Round Number Operation On Students’ Learning Achievement Of Mathematics in High Class at SD Inpres Lelumpang.